Makna Sakral Siklus Pertanian di Tana Persekutuan Detunggali: Sebuah Kajian Etnografi Ritus Agraris - Fransiskus Saverius Minggu; Yulianus Kian; Jefrianus Ulu Manek; Paskalis Jhon juan; Frederikus Rifaldo Soro; Robertho Mario Wetan Kwure (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
This study examines the sacred meaning of the agricultural cycle in the life of the indigenous community of the Detunggali Communal Land through an ethnographic approach. Agricultural rituals accompanying all stages of farming from land clearing, seed preparation and planting, crop maintenance, to harvesting are understood as cultural practices that integrate spiritual, social, and ecological dimensions. The study aims to explore how these agrarian rites function in shaping relationships between humans, nature, and ancestors, while sustaining the collective identity of the Detunggali community. A qualitative descriptive method was employed, with data collected through in-depth interviews, participant observation, and documentation involving customary elders and community members. The findings reveal that farming activities in Detunggali are not merely economic endeavors but are deeply embedded in sacred values expressed through symbols, prayers, and customary rules. Agrarian rituals play a crucial role in maintaining cosmic balance, strengthening social cohesion, and fostering ecological awareness rooted in local cosmology. The study highlights that indigenous agricultural traditions remain a vital source of cultural and spiritual values, offering important insights for cultural preservation and locally grounded approaches to sustainable development.